2022
DOI: 10.1007/s00408-022-00557-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Domiciliary Non-Invasive Ventilation Compliance

Abstract: Few international studies have investigated factors affecting domiciliary non-invasive ventilation (D-NIV) compliance, and data from the UK are limited. We assessed compliance (defined as ≥ 4 h/night for at least 70% of the time) in a retrospective UK population study, at three time points (0–1 month, 3–4 months and 11–12 months), for all patients commenced on D-NIV over a 5-year period. A total of 359 patients were included. Non-compliant vs. compliant patients were significantly younger (median age 64 (IQR 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Psychosocial aspects including the effects of treatment burden especially in patients with multimorbidity can impact adherence [ 76 ]. Patients who are younger, have a mental health diagnosis, and are from socioeconomically deprived backgrounds may need additional support to promote adequate HMV compliance [ 77 ].…”
Section: Applications Of Home Mechanical Ventilationmentioning
confidence: 99%
“…Psychosocial aspects including the effects of treatment burden especially in patients with multimorbidity can impact adherence [ 76 ]. Patients who are younger, have a mental health diagnosis, and are from socioeconomically deprived backgrounds may need additional support to promote adequate HMV compliance [ 77 ].…”
Section: Applications Of Home Mechanical Ventilationmentioning
confidence: 99%
“…In the study of Slot et al, they identified that patients living with a partner were almost five times more likely to adhere to treatment [ 17 ]. Mental health diagnoses appear to be associated with poor usage; for example, people with depression [ 17 , 18 ] and schizophrenia have been shown to have lower NIV usage [ 16 ]. The type of mask has not been demonstrated to affect usage [ 15 ].…”
mentioning
confidence: 99%
“…We remain eager to increase publication of high-quality manuscripts in the fields of Critical Care and Pediatric Pulmonology, and invite prospective authors to submit their work for consideration. Studies examining issues in critical illness included intravascular volume management in acute pulmonary embolism [ 68 ]; liver transplantation [ 69 ]; non-invasive ventilation [ 70 , 71 ]; pulmonary effects of anesthesia [ 72 ]; and, a preclinical examination of acute lung injury [ 67 ]. Investigations of pediatric populations included topics such as management of bronchopulmonary dysplasia [ 73 ], interstitial lung disease [ 46 ] and asthma [ 17 ].…”
mentioning
confidence: 99%